Environmental sustainability, sugar consumption, and SodaStream - Osland, Asbjorn, (SAGE Knowledge. Cases., 2019)
SodaStream manufactures and sells a device for creating carbonated flavored beverages at home. It became an Israeli company in 1998. The Israeli leadership of the firm thought that reducing plastic waste would be a good marketing tool given that SodaStream does not use disposable bottles. The specific focus was reduction of plastic waste, contained within the broader concept of environmental sustainability. The company ran advertisements that were pointedly critical of large beverage companies that used disposable plastic bottles. The message to the consumer was: waste less plastic by using SodaStream and thereby support environmental sustainability. Would environmental sustainability make SodaStream the choice of consumers who were concerned about plastic waste? Some environmentally-concerned consumers would see SodaStream as beneficial in this regard, but the mass market showed little concern about plastic waste; people in the United States continue to purchase beverages in disposable bottles.Another advertising focus could be sugar content in beverages. This alternative focus could prove more compelling to a mass-market advertisement campaign than plastic waste in that sugar consumption is one reason the United States is experiencing an obesity epidemic. SodaStream offers a way to control sugar intake.Students are asked to evaluate the intertwined issues of plastic waste, sugar and obesity, consumer concerns, and advertisements.